Regional gray matter-dedicated SUVR with 3D-MRI detects positive amyloid deposits in equivocal amyloid PET images - Ishii, Kazunari; Yamada, Takahiro; Hanaoka, Kohei; Kaida, Hayato; Miyazaki, Koichi; Ueda, Masami; Hanada, Kazushi; Saigoh, Kazumasa; Sauerbeck, Julia; Rominger, Axel; Bartenstein, Peter; Kimura, Yuichi (Annals of nuclear medicine, 2020)
Purpose It is usually easy to judge whether amyloid PET images should be interpreted as positive or negative for amyloid deposits by visual inspection or quantitative measurement standard uptake value ratio (SUVR), but the findings are equivocal in some cases. As conventional mean cortical SUVR (mcSUVR) measures accumulation in both gray matter (GM) and white matter, it may mis-estimate amyloid deposits. The purpose of the study was to develop a regional GM-dedicated SUVR measuring (GMSUVR) system for amyloid PET images with 3D-MRI, and evaluate its utility for detecting amyloid deposits in equivocal cases. Methods Of 126 subjects who underwent amyloid PET with 11 C-PiB and 3D-MRI, the area of amyloid-positive regions and the critical regional GMSUVR thresholds were first determined in 15 amyloid-positive and 15 amyloid-negative patients, using the automatic volumetric measurement of segmented brain images system. We then tested 36 amyloid-negative, 60 amyloid-positive, and 13 equivocal subjects with this GMSUVR system and with conventional mcSUVR. Results Sensitivity, specificity, accuracy, positive predictive value (PPV) and negative predictive value (NPV) were 100%, 92%, 97%, 95%, and 100% for the GMSUVR system; and 97%, 86%, 93%, 92% and 94%, respectively, for mcSUVR. In 24 cases in which the findings were equivocal or discordant, the sensitivity, specificity, accuracy, PPV, and NPV were all 100% for the GMSUVR system; and were 90%, 33%, 83%, 90%, and 33%, respectively, for mcSUVR. Conclusion The regional GMSUVR measurement method was well able to discriminate between amyloid-positive and -negative subjects, even in cases where amyloid deposition was equivocal.